2019
DOI: 10.1073/pnas.1903610116
|View full text |Cite
|
Sign up to set email alerts
|

Power quality and modern energy for all

Abstract: “Modern energy for all,” an internationally supported initiative to connect populations to electricity services, is expected to help reduce poverty-induced vulnerabilities. It has become a primary strategy for meeting sustainable development goals, especially in sub-Saharan Africa. However, when electricity is supplied by a capacity-constrained grid to a resource-constrained population, the service quality can vary both spatially and temporally. This research explores the quality of electricity services based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…and demand is making grid extension unviable. This finding is in line with literature, for instance in Tanzania a study revealed low of voltage as a major deprivation for household and businesses on the Island of Zanzibar (Jacome et al, 2019). Similar limitations have been found in literature (Dasso and Fernandez, 2015).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…and demand is making grid extension unviable. This finding is in line with literature, for instance in Tanzania a study revealed low of voltage as a major deprivation for household and businesses on the Island of Zanzibar (Jacome et al, 2019). Similar limitations have been found in literature (Dasso and Fernandez, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…A good example is in South Africa, where an initiative was put in place to transfer 1.7 million residents from informal to a formalized housing settlement before electrification could take place (Niez, 2010). Furthermore, poor quality of voltage was identified in Tanzania as a constraint on the Island of Zanzibar (Jacome et al, 2019). Relatedly, many other studies reveal that, most households in SSA install low-capacity solar products, which by world bank standards are considered no access (Coville et al, 2019;Grimm, et al, 2016;Bensch, et al, 2018).…”
Section: Market Potential For Solar Photovoltaic System (Electricity mentioning
confidence: 99%
“…With respect to the "Harvard dataverse", fifty records were found that contained power quality in the name, but only four of them were related to the electrical field. The four datasets belonged to the same category: "Power Quality and Modern Energy for All" [26]. However, they included voltage data without mentioning specific power quality distortions.…”
Section: A Selection Proceduresmentioning
confidence: 99%
“…Thus, a caveat is that our estimates measure the infrastructural dimension of electricity access, more than the policyand financing-related issues that governments and electrification programs must tackle to enable new connections of households living in the proximity of the grid but facing financial and behavioral barriers. 67 Finally, nighttime light data largely capture radiance between 0:00 and 4:30 a.m., when most residential indoor lights are turned off. Thus, the approach is effective in those settlements where at least minimal amounts of street or public lighting are available.…”
Section: Uncertainty and Limitationsmentioning
confidence: 99%